Managing Transitions : Reaching the Vulnerable while Pursuing Universal Health Coverage - World Bank Group (World Bank, Washington, DC, 2017)
As Lao PDR prepares to graduate from Least Developed Country (LDC) status by 2020 to become an upper-middle-income country by 2030, it also expects to face declining funding from external sources and the need to increase domestic financing for health. This report aims to provide a snapshot of the current health financing system of Lao PDR and to identify critical constraints and opportunities facing the health care system as the country undergoes transitions in demographics, epidemiology and health financing. In addition to reviewing the overall health financing system, the report includes an in-depth analysis of key bottlenecks and sustainability challenges for immunization services as a marker for implementation constraints in the face of rapidly reducing external financing.